Retrospective study comparing three approaches for keloids: surgery + radiotherapy, surgery + pharmacological injection, and surgery alone - ShengHua Chen; Xu Mu; Lin Zhang; Wei Liu; YuYang Han; Hanhua Li; Wen Lai; Zhifeng Huang (BMC Surgery)
Abstract Objective To investigate the differential efficacy of various treatment modalities adjunct to surgical excision of keloids and to analyze prognostic factors influencing outcomes. Methodology A retrospective observational study approach was employed. Clinical data from 121 patients with keloids who met the inclusion criteria were collected for analysis of clinical characteristics and evaluation of treatment efficacy. The patients were categorized into three groups based on the adjuvant treatment modalities utilized post-surgical excision of keloids: surgical + radiotherapy group (group A), surgical + radiotherapy + pharmacological injection group (group B), and surgical group (group C). Factors potentially influencing treatment outcomes—such as treatment modality, gender, age, lesion distribution, lesion size, duration of the condition, and prior treatments—were subjected to a statistical analysis. Significant risk factors were identified through univariate analysis. Results The efficacy rates for group A, group B, and group C were 93.88%, 87.04%, and 55.56%, respectively. Statistical analysis indicated that age and treatment modality were significant risk factors for recurrence. Conclusion The application of radiotherapy post-surgery, or a combination of radiotherapy and pharmacological injections postoperatively, has been demonstrated to significantly reduce the recurrence rate of keloids. Conversely, the efficacy of treatments that solely rely on surgery is comparatively lower. For elderly patients, early intervention upon the manifestation of clinical symptoms is strongly advocated, with a preference for adjunctive postoperative radiotherapy to mitigate the risk of recurrence.